Tata Kelola Stakeholder dalam Meningkatkan Mutu Pendidikan Pada Madrasah Tsanawiyah - Ihsan Muhadi; Giyoto Giyoto; Lilik Untari (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine stakeholder governance in improving the quality of education at Madrasah Tsanawiyah (MTs) Negeri 1 Sukoharjo. This governance includes the management of teaching staff and education personnel in improving the quality of secondary education at MTs Negeri 1 Sukoharjo, student management in improving the quality of secondary education at MTs Negeri 1 Sukoharjo, governance of partner communities and graduate users in improving the quality of secondary education at MTs Negeri 1 Sukoharjo. The methodology in this study uses a qualitative approach. Data collection techniques in this study include observation, in-depth interviews, FGD (Focus Group Discussion), and document review. Data analysis in this study was carried out in 4 (four) steps, namely: 1) performing data management, 2) writing memos on the edge of field notes or transcripts to assist database exploration, 3) delineation, classification, and interpretation, and 4) visualization and representation findings. The results showed that the governance of stakeholders in improving the quality of education at Madrasah Tsanawiyah (MTs) Negeri 1 Sukoharjo which includes the management of teachers and education personnel, student governance, and how madrasahs manage the role of stakeholders in improving the quality of secondary education at Madrasah Tsanawiyah ( MTs) Negeri 1 Sukoharjo is done very well so that the quality of education at Madrasah Tsanawiyah (MTs) Negeri 1 Sukoharjo is very good.